Determining oxidation states of transition metals in molten salt corrosion using electron energy loss spectroscopy. (May 2021) - Bawane, Kaustubh; Manganaris, Panayotis; Wang, Yachun; Sure, Jagadeesh; Ronne, Arthur; Halstenberg, Phillip; Dai, Sheng; Gill, Simerjeet K.; Sasaki, Kotaro; Chen-Wiegart, Yu-chen Karen; Gakhar, Ruchi; Mahurin, Shannon; et al.
Abstract: This work utilizes electron energy loss spectroscopy (EELS) to identify oxidation state of alloying elements in Ni-based alloys after exposure to molten chloride salt systems. Pure Ni and Ni-20Cr model alloy were corroded in molten ZnCl2 and KCl-MgCl2 under argon atmosphere at various temperatures. Oxidation states of Cr (Cr 3+ ) and Ni (Ni 2+ ) in the molten salt after corrosion were determined by monitoring changes in the L2, 3 edges of corresponding EELS spectra. Oxidation state mapping technique using principal component analysis and multiple linear least squares fitting in HyperSpy Python package was developed. Graphical Abstract: Image, graphical abstract